Literature Review: Perbandingan Efektivitas Pemberian Microwave Diathermy dengan Infra Red terhadap Pengurangan Nyeri Osteoartritis Lutut - Nur Halisa Amalia; Muhammad Siddik; Didik Dwi Sanyoto; Bambang Dwi Putranto; Husna Dharma Putera (Homeostasis, 2022)
Abstract: Knee osteoarthritis (OA) is the most common knee pain complaint. Non pharmacological therapy, including microwave diathermy therapy (MWD) and infra red therapy (IR) is one of the treatment options. Both work in tissue repair, increase metabolic processes, and reduces inflammation in knee OA by electromagnetic radiation hyperthermia. The purpose of this literature review was to analyze comparison of the effectiveness of MWD and IR in reducing pain intensity in knee OA patients. The data were collected by analyzing literature from several databases, namely PubMed-NCBI, ProQuest, Science Direct, and Google Scholar. The criteria for inclusion of articles are articles in English and Indonesian in research published in 2011–2021. In this literature review, 8 articles were used. According to the findings of the review, MWD and IR were both effective in reducing pain in knee OA patients. Three of the five MWD articles showed that reducing pain intensity of knee OA was more effective. Two of the three IR articles showed that reducing pain intensity of knee OA was more effective. It may be concluded that IR therapy is better than MWD therapy in reducing pain knee OA based on the average score of pain parameters using VAS before and after therapy. Keywords: effect, microwave diathermy, infra red, pain, knee osteoarthritis Abstrak: Osteoartritis lutut (OA) adalah keluhan nyeri lutut yang paling umum. Salah satu pengobatan yang dapat dilakukan adalah terapi non farmakologi yaitu terapi microwave diathermy (MWD) dan terapi infra red (IR). Keduanya memiliki kesamaan dalam hipertermia radiasi elektromagnetik, dan berfungsi perbaikan jaringan, peningkatan proses metabolisme, dan pengurangan inflamasi OA lutut. Tujuan Literature review ini untuk membandingkan efektivitas MWD dan IR dalam mengurangi intensitas nyeri pada pasien OA lutut. Penulisan dilakukan dengan menganalisis literatur dari beberapa database jurnal kedokteran elektronik, yaitu: PubMed-NCBI, ProQuest, Science Direct dan Google Scholar. Kriteria pencantuman artikel adalah artikel berbahasa Inggris dan Indonesia dalam penelitian yang diterbitkan tahun 2011–2021. Ada 8 artikel yang digunakan dalam literature review ini. Hasil tinjauan menemukan bahwa MWD dan IR keduanya efektif dalam mengurangi rasa nyeri pada pasien OA lutut. Tiga dari lima artikel MWD menunjukkan hasil yang lebih efektif dalam mengurangi intensitas nyeri OA lutut. Dua dari tiga artikel IR menunjukkan hasil yang lebih efektif dalam mengurangi intensitas nyeri OA lutut. Berdasarkan dari rata-rata skor parameter nyeri dengan VAS sebelum dan sesudah terapi, dapat disimpulkan bahwa pemberian terapi IR lebih baik daripada pemberian terapi MWD terhadap pengurangan nyeri OA lutut. Kata-kata kunci:   effect, microwave diathermy, infra red, pain, knee osteoarthritis